38.8k views
1 vote
The functions f and g are defined as follows( view the image attached)

The functions f and g are defined as follows( view the image attached)-example-1
User Carpenter
by
5.1k points

1 Answer

4 votes

Answer

f(-3) = 36

g(6) = - 10

Step-by-step explanation:

Given the following functions

f(x) = 3x^2 - 3x

g(x) = -2x + 2

Find f(-3) ?

f(-3) means substitute x = -3

f(-3) = 3(-3)^2 - 3(-3)

f(-3) = 3(9) + 9

f(-3) = 27 + 9

f(-3) = 36

g(6) = -2(6) + 2

g(6) = -12 + 2

g(6) =- 10

Therefore, f(-3) = 36 and g(6) = -10

User Mynkow
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.